Buried free flaps in head and neck surgery: Outcome analysis. Issue 10 (13th September 2012) - Lindau, Robert H.; Detwiller, Kara; Wax, Mark K.
<x xml:space="preserve">Abstract</x> Background Over the last several decades, reconstruction of the head and neck oncologic defect has been revolutionized by the use of microvascular free tissue transfer. The majority of these defects can be reconstructed with the ability to visually monitor the flap, to intervene as soon as vascular compromise becomes evident. Occasionally, it is necessary to use a flap that has no visual external monitor: a buried free flap. A belief has circulated within the microvascular community that buried free flaps do not do as well as visible flaps. By our review, there are no recent data in the literature to support this position. We present our data on the outcomes of buried free flaps in microvascular reconstruction. Methods A single institutional retrospective review of 1492 flaps was performed between January 1999 and December 2011. A total of 103 free flaps (7.2%) were identified as meeting the criteria for a buried flap. It should be noted that all flaps with or without an external segment were monitored with an implantable Doppler. The flap failure and complications are defined as those failures or complications occurring within 2 weeks of surgery and related to the operation or to the flap itself. Results In all, 5 of the 103 patients (4.9%) had complications requiring reoperative intervention. There were no instances of flap failure within the first 2 weeks of surgery. Conclusion In our series, there are no differences in flap failure rates comparing buried flaps to externally monitored flaps. © 2012 Wiley Periodicals, Inc. Head Neck 35: 1468–1470, 2013